2020
DOI: 10.3390/s20216010
|View full text |Cite
|
Sign up to set email alerts
|

A Wearable Sensor System for Physical Ergonomics Interventions Using Haptic Feedback

Abstract: Work-related musculoskeletal disorders are a major concern globally affecting societies, companies, and individuals. To address this, a new sensor-based system is presented: the Smart Workwear System, aimed at facilitating preventive measures by supporting risk assessments, work design, and work technique training. The system has a module-based platform that enables flexibility of sensor-type utilization, depending on the specific application. A module of the Smart Workwear System that utilizes haptic feedback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(79 citation statements)
references
References 81 publications
2
76
1
Order By: Relevance
“…No included study reported post-intervention monitoring to assess the retention of improvements following WIST feedback. Four types of feedback prompts were identified throughout the included studies: auditory [ 68 , 71 , 73 , 74 , 75 , 80 ]; vibrotactile (haptic) [ 69 , 72 , 74 , 76 , 77 , 78 , 79 ]; visual [ 67 , 70 , 71 , 72 , 74 , 75 , 78 ] and summary feedback (visual) [ 74 ]. The most common multimodal feedback interaction was auditory and visual [ 71 , 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No included study reported post-intervention monitoring to assess the retention of improvements following WIST feedback. Four types of feedback prompts were identified throughout the included studies: auditory [ 68 , 71 , 73 , 74 , 75 , 80 ]; vibrotactile (haptic) [ 69 , 72 , 74 , 76 , 77 , 78 , 79 ]; visual [ 67 , 70 , 71 , 72 , 74 , 75 , 78 ] and summary feedback (visual) [ 74 ]. The most common multimodal feedback interaction was auditory and visual [ 71 , 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most common multimodal feedback interaction was auditory and visual [ 71 , 74 , 75 ]. Most studies applied concurrent bandwidth feedback [ 67 , 69 , 73 , 75 , 76 , 77 , 79 , 80 ] (i.e., a feedback prompt when a movement variable exceeds a pre-determined set-point (feedback trigger) during the activity/task [ 131 , 132 ]; and in conjunction with a pre-determined time period [ 68 , 71 , 72 , 74 , 78 ] ( Table 4 ); the remaining studies used terminal bandwidth feedback (feedback post-activity) [ 70 ] and summary feedback in addition to visual, auditory and vibrotactile feedback [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To meet the demands of a comprehensive risk assessment, the greatest advantage is advancements in technology which allow for even further possibilities than we have proposed. Risk assessment systems or tools might also take multimodal input (i.e., auditory, visual, physiological) through sensor systems built specifically for risk assessment ( 36 ). The information from these systems could then be added to the Work Characteristics matrix derived from the video recordings.…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies using integrated sensors in IMUs increased after 2016 ( Table 1 ). Given the increase in the use of IMUs, this information is also needed when comparing new IMU-based measurements as in, e.g., Lind et al [ 42 ], Lind et al [ 43 ], to the recommended threshold limit values based on accelerometer-based measurements [ 14 ]. Moreover, this information can also be used for merging results from older and more recent studies to increase the precision on the associations between inclinations and angular velocities of arms and trunk, and MSDs.…”
Section: Introductionmentioning
confidence: 99%